A triple chain polycationic peptide-mimicking amphiphile – efficient DNA-transfer without co-lipids. (4th November 2019) - Pinnapireddy, Shashank Reddy; Giselbrecht, Julia; Strehlow, Boris; Janich, Christopher; Husteden, Catharina; Meister, Annette; Loppnow, Harald; Sedding, Daniel; Erdmann, Frank; Hause, Gerd; Brezesinski, Gerald; Groth, Thomas; et al.
Abstract : DiTT4 lipoplexes have exhibited excellent transfection efficiency in a complex tissue together with a biocompatibility profile that makes it a prospective vehicle for gene delivery. Abstract : Non-viral gene delivery in its current form is largely dependent upon the ability of a delivery vehicle to protect its cargo in the extracellular environment and release it efficiently inside the target cell. Also a simple delivery system is required to simplify a GMP conform production if a marketing authorization is striven for. This work addresses these problems. We have developed a synthetic polycationic peptide-mimicking amphiphile, namely DiTT4, which shows efficient transfection rates and good biocompatibility without the use of a co-lipid in the formulation. The lipid–nucleic acid complex (lipoplex) was characterized at the structural (electron microscopy), physical (laser Doppler velocimetry and atomic force microscopy) and molecular levels (X-ray scattering). Stability studies of the lipoplexes in the presence of serum and heparin indicated a stable formation capable of protecting the cargo against the extracellular milieu. Hemocompatibility studies (hemolysis, complement activation and erythrocyte aggregation) demonstrated the biocompatibility of the formulation for systemic administration. The transfection efficiency was assessed in vitro using the GFP assay and confocal laser scanning microscopy studies. With the chorioallantoic membrane model, an animal replacement model according to the 3R strategy (replacement, refinement, and reduction), initial in vivo experiments were performed which demonstrate fast and efficient transfection in complex tissues and excellent biocompatibility.